The impact of tax administration digitalization on taxpayer behavior: A comprehensive review of previous studies - Saida Slimani, Issam Abidli (International journal of economic perspectives, 2025)
Purpose: This study aims to explore the impact of tax administration digitalization on taxpayers’ behavior, highlighting its role in enhancing tax compliance and promoting positive behavioral changes among taxpayers. Importance/Value: The research emphasizes the strategic importance of digitalizing tax processes as an essential tool for improving the efficiency and effectiveness of tax administration. It contributes uniquely by demonstrating how digitalization aligns with theoretical frameworks to strengthen compliance mechanisms and foster trust between taxpayers and administrations. Methodology/Approach: The study employs a bibliometric analysis to examine a sample of 23 prior studies retrieved from the Scopus database. Descriptive and analytical approaches were utilized to assess the influence of tax administration digitalization on taxpayers’ behavior. Findings: The findings reveal a positive relationship between tax administration digitalization and improved taxpayer behavior. The results support the theoretical frameworks applied, demonstrating how digitalization enhances compliance while reducing tax-related disputes and complexities. Conclusion: The study concludes that digitalization of tax administration is a transformative approach that significantly contributes to tax compliance and behavioral improvements, ultimately benefiting the overall tax system’s efficiency. Recommendations: The study recommends investing in the modernization of tax administration infrastructure, developing advanced digital tools, and implementing policies that encourage voluntary compliance to build stronger trust between taxpayers and tax authorities.